Accuracy of international ultrasound risk stratification systems in thyroid lesions cytologically classified as indeterminate. Issue 2 (26th December 2016) - Trimboli, Pierpaolo; Fulciniti, Franco; Zilioli, Valentina; Ceriani, Luca; Giovanella, Luca
Abstract : Background: Eminent international societies have published their thyroid ultrasound risk stratification system (US‐RSS) to give a friendly tool for thyroidologists. In particular, American Thyroid Association (ATA), American Association Clinical Endocrinologists/American College of Endocrinologists and Associazione Medici Endocrinologi (AACE/ACE/AME), British Thyroid Association (BTA), and Thyroid Imaging Reporting and Data System (TIRADS) are often adopted for clinical practice. The reliability of these US‐RSS has not been evaluated in discriminating cancers from benignancy in nodules with indeterminate FNA. Methods: Indeterminate thyroid lesions were searched in our database and only those with histology were finally included. The matching of US and histologic data of nodule's location and size were verified. All US images and clips were re‐evaluated and nodules classified according to the above US‐RSS. Results: A series of 101 indeterminate lesions, diagnosed by FNA were included (mean size 2.4 cm) and a 21% of cancers was found at histology. When all lesions were classified by US‐RSS, poor accuracy (up to 54%) and specificity (up to 19%) were recorded. Highest sensitivity (91%) and NPV (94%) was obtained by BTA. Of relevance, the rate of nodules with indeterminate US risk recorded by BTA was significantly lower than the other ( P  < 0.001). At nodule's size analysis, cancers had significantly higher estimated volume ( P  < 0.05). When we considered the size thresholds proposed by guidelines, ATA system reached the highest sensitivity in detecting cancers (95%). Conclusions: Even if international US‐RSS have suboptimal accuracy in indeterminate thyroid nodules, high sensitivity can be obtained using ATA system with specific dimensional cut‐offs. Diagn. Cytopathol. 2017;45:113–117. © 2016 Wiley Periodicals, Inc.